Genetic improvement of Traits in Khatooni Melon using Mass selection in Iran - Sobhani, Alireza; Bashtani, Ebrahim; Rafezi, Ramin (Asian Journal of Biological and Life Sciences, 2016)
High genetic diversity of Melon (Cucumismelo L.) in Iran and cross pollination of this product over the last years has led to serious genetic erosion.In order to improve average desirable traits of Iranian Khatooni melon, a field experiment conducted in Mashhad and Torbate-jam based on two selection periods. Studied traits included yield, earliness, fruit weight, the number of fruit, flesh and skin diameter, sugar content, fruit length and width, flesh and skin weight, and seed weight. Fruit yield in modified genotype increased 11.92% and 33.49% respectively after one and two period selection compared to primary genotype. Also fruit weight increased 24.3% in modified genotype after two period selection compared to primary genotype. In the present study, modified Khatooni cultivar compared with two other genotypes included primary Khatooni and imported Khatooni melon with Argon brand in two locations of Mashhad and Torbate-jam. Results showed that there was no significant difference between Mashhad and Torbate-jam in terms of yield. Fruit yield of melon in Torbate-jam (29.35 ton.ha-1)was greater than Mashhad (26.69 ton.ha-1) consequence of higher average fruit weight of melon in Torbate-gam.
Keywords: Breeding; Fruit Quality; Melon; Sugar content; Yield component